THREE DIMENSIONAL MODELING OF KRAKATOA VOLCANO SUBSURFACE STRUCTURE USING GRAVITY METHOD - VALLERIE OEMAIYA - NIM: 12313037 , DEA
Gravity method is one of geophysical methods based on measurements of the gravitational field to discover subsurface model. The principle is to distinguish between the material’s density to the environment. From this differences, the subsurface structutre can be modeled. Gravity method can be used for both oil and mineral exploration. Density contrast is a sign of anomalous gas, oil and other materials presence, including magma. Magma is a high temperature and complex silicate solutions in the bowels of the earth. Magma’s density is one of significant parameters for understanding the process of volcano activity. Krakatoa Volcano has a fairly unique magma chamber which is not located just below Krakatoa Volcano, so the low gravity anomaly won‘t be located below Krakatoa Volcano. Currently Krakatoa Volcano has multiple magma chamber manifold andesite magma with density value 2.5 g/cc. The differences of magma‘s density and rock’s density surround it can be used as parameters in modeling of Krakatoa Volcano subsurface structure. To determine this, regional anomalies and residual anomalies separation is necessary, then combine it with geological and geophysical data.